Inoculation works and health advocacy backfires: Building resistance to COVID-19 vaccine misinformation in a low political trust context - Jiang, Li Crystal; Sun, Mengru; Chu, Tsz Hang; Chia, Stella C. (Frontiers in Psychology, 2022)
This study examines the effectiveness of the inoculation strategy in countering vaccine-related misinformation among Hong Kong college students. A three-phase between-subject experiment (n = 123) was conducted to compare the persuasive effects of inoculation messages (two-sided messages forewarning about misinformation related to COVID-19 vaccines), supportive messages (conventional health advocacy), and no message control. The results show that inoculation messages were superior to supportive messages at generating resistance to misinformation, as evidenced by more positive vaccine attitudes and stronger vaccine intention. Notably, we did not detect any significant outcome difference between the inoculation and control conditions. Attitudinal threat and counterarguing moderated the experimental effects; issue involvement and political trust were found to directly predict vaccine attitudes and intention. The findings suggest that future interventions focus on developing preventive mechanisms to counter misinformation and spreading inoculation over the issue is an effective strategy to generate resistance to misinformation. Interventions should be cautious about using health advocacy initiated by governments among populations with low political trust.